Organizational Culture as The Basis of Teacher Performance Development - Santosa, Achadi Budi (JURNAL AL-TANZIM, 2022)
This study not only measures the relationship between organizational culture and teacher performance but also finds an essential foundation for madrasah in building organizational culture and how to improve their performance. A descriptive quantitative approach is used in this research; data collection is done through surveys and the preparation of research instruments. The results show that, in general, the organizational culture is quite good, the values, teamwork, and work performance are also good, while in performance, teachers generally have various levels of achievement, satisfaction, responsibility, honesty, empathy, and persistence in work. In madrasah, organizational culture is related to teacher performance so a superior organizational culture will affect teachers' performance; on the other hand, educational institutions that cannot build a good culture result in decreased teacher performance.